Posterior Cervical Keyhole Foraminotomy in Treatment of Cervical Radiculopathy Following Anterior Cervical Discectomy and Fusion - Hazem Negm (Egyptian Spine Association, 2017)
Background Data: Cervical radiculopathy after prior anterior cervical discectomy may result from residual compression after the first surgery or development of new compression at the same level or an adjacent level. Treatment for recurrent or residual symptoms can involve conservative measures or surgery. The anterior approach may be used with ease for the treatment of fresh level disc disease although it may be difficult in recurrent or residual situations. Purpose: To describe the surgical outcome of posterior keyhole foraminotomy with or without discectomy for treatment of cervical radiculopathy following anterior cervical discectomy and fusion (ACDF). Study Design: Retrospectively analysis of a prospectively collected database of a consecutive series of patients. Patients and Methods: We included patients that had undergone microscopic posterior cervical keyhole foraminotomy with or without discectomy surgeries for residual or recurrent cervical radiculopathy after prior ACDF. Patients with central canal compression were excluded. The site of recurrence and outcome after surgery has been reported and correlated with the procedure performed. The clinical outcome was evaluated by pain Visual Analogue Score (VAS), Neck Disability Index (NDI) and Oswestry Disability Index (ODI). Postoperative complications were reported. Chi-Square or Fisher exact test was used to compare categorical variables and Mann–Whitney U test was used to compare continuous variables. Results: we identified twenty-one patients who had 24 posterior cervical keyhole foraminotomies (18 single and 3 double level) after prior anterior cervical discectomy and fusion (19 single and 2 double level) through 2013 to 2016. In 12 patients (57%), the complaint was related to the primary level, of whom 3 patients had additional level to the primary one. Nine patients (43%) had a complaint related to the new disc level other than the primary level of surgery. The clinical outcome was generally satisfactory, where pain VAS, Neck Disability Index (NDI) and Oswestry Disability Index (ODI) were significantly reduced after surgery. Eighteen (85.7%) patients had an excellent or good clinical outcome. Two patients had wound infection and one patient had wound hematoma, all treated conservatively. No neurologic deficit has resulted from the posterior cervical keyhole foraminotomy. No postoperative mortality. No recurrence of symptoms has been reported trough the period of follow up.Conclusion: Microscopic posterior cervical keyhole foraminotomy with or without discectomy is a safe and effective procedure in the treatment of recurrent or residual cervical radiculopathy following prior anterior cervical discectomy and fusion. (2017ESJ138)